Relativistic electron dynamics produced by azimuthally localized poloidal mode ULF waves: Boomerang‐shaped pitch angle evolutions. Issue 15 (12th August 2017) - Hao, Y. X.; Zong, Q.‐G.; Zhou, X.‐Z.; Rankin, R.; Chen, X. R.; Liu, Y.; Fu, S. Y.; Spence, H. E.; Blake, J. B.; Reeves, G. D.
Abstract: We present an analysis of "boomerang‐shaped" pitch angle evolutions of outer radiation belt relativistic electrons observed by the Van Allen Probes after the passage of an interplanetary shock on 7 June 2014. The flux at different pitch angles is modulated by Pc5 waves, with equatorially mirroring electrons reaching the satellite first. For 90° pitch angle electrons, the phase change of the flux modulations across energy exceeds 180° and increasingly tilts with time. Using estimates of the arrival time of particles of different pitch angles at the spacecraft location, a scenario is investigated in which shock‐induced ULF waves interact with electrons through the drift resonance mechanism in a localized region westward of the spacecraft. Numerical calculations on particle energy gain with the modified ULF wavefield reproduce the observed boomerang stripes and modulations in the electron energy spectrogram. The study of boomerang stripes and their relationship to drift resonance taking place at a location different from the observation point adds new understanding of the processes controlling the dynamics of the outer radiation belt. Key Points: Boomerang‐shaped pitch angle evolutions of relativistic electrons in Pc5 band is observed for the first time in the outer radiation belt Electrons' drift resonating with azimuthally localized ULF waves can produce boomerang‐shaped pitch angle stripes Nonlocal effects in drift‐resonant process on outer belt dynamics